DIPLOMASI PUBLIK PEMERINTAH REPUBLIK INDONESIA MELALUI PARIWISATA HALAL - Garit Bira Widhasti; Christy Damayanti, Herning Suryo Sardjono (Solidaritas, 2017)
DIPLOMASI PUBLIK PEMERINTAH REPUBLIK INDONESIA MELALUI PARIWISATA HALAL Garit Bira WidhastiChristy DamayantiHerning Suryo SardjonoProgram Studi Ilmu Hubungan Internasional Fakultas Ilmu Sosial Dan Ilmu PolitikUniversitas Slamet Riyadi Surakarta ABSTRACTThis research aims to explain the existence of tourism as Indonesian soft power which developed through Halal Tourism as part of Indonesian public diplomacy. Indonesia seeks to shape perception of international Muslim society through tourism that brings Islamic value, cultural value, and universal value that is believed to be more readily accepted by the society as well as the belief that tourism is an activity that will facilitate the communication process between government and the society. The explaination of public diplomacy by Indonesian government through Halal Tourism will be done with the englighten of the Halal Tourism campaign activity and its development. By using the theory of public diplomacy and nation branding, this research make use of qualitative method with primary data document-based research and explained by descriptive method. Through analysis of Halal Tourism campaign activity, the researcher concludes that the public diplomacy by Indonesian government through Halal Tourism campaign towards the Middle East’s Muslim society was established to embed, to emerge, and to evolve the positive image of Indonesia. In the progress, public diplomacy through Halal Tourism reinforce Indonesian position in Global Muslim Tourism Index, escalate Indonesian achievement in World’s Halal Tourism Award, and increase the number of Muslim tourist arrival. Key word: Soft Power, Public Diplomacy, Halal Tourism, Indonesian Image